Teaching, Research, Service and PAR - Robinson, Mike (ARCTIC, 1998)
. Over the past decade, AINA has contributed in all three areas (teaching, research and service), benefiting from association with its host university. We are now a nationally recognized centre of teaching and practice for participatory action research (PAR), known for our innovative combination of undergraduates, graduate students, and research associates in the conduct of international PAR projects. The last few years found our PAR teams in the Kola Peninsula in Russia, the back country of Nicaragua, the tundra of Holman Island, the Dene hearland of the Northwest Territories, and the boreal forest zone of northern Alberta and British Columbia. . Collectively we have all benefited from the PAR methodology, and now we are sharing our methodological experience and participatory competence with several research and advocacy organizations in different parts of the globe. Chief amongst these at present are the International Foundation for Socio-Economic and Political Studies of the Gorbachev Foundation of Moscow, the David Suzuki Foundation of Vancouver, and the Instituto de Medicina Tradicional Y Desarrollo Comunitario of Nicarauga. We are always ready to share our experience with you, . Is there a PAR project in your backyard?